2020
DOI: 10.1007/s11249-020-01338-1
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Synergy of Blended Lithium Complex Soap and Calcium Sulfonate Towards Good Lubrication and Anti-Corrosion Performance

Abstract: Thickener plays a significant role on the performance of grease, including rheological property, chemical and thermal stability, colloidal and mechanical stability, and so forth. Here, lithium complex-calcium sulfonate (L/C) greases were synthesized via regulating lithium complex soap and calcium sulfonate in the molar ratio of 1:2, 2:1 and 1:1, along with thickening the polyalphaolefin (PAO40). The physicochemical properties, corrosion resistance and tribological performance were evaluated in detail, with lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As shown in Table 3, the factors that may affect the tribological properties and service life of lubricating grease during the preparation process of CSCPG are listed, including the proportion of three thickening agents [29]: overbased calcium sulfonate T106A (coded A), polyurea thickening agent (coded C), and composite calcium soap (coded D); base oil 40 • C kinematic viscosity (coded B) [14]; the proportion of the content of the two additives: antioxidant (coded E) [30] and nano-solid friction reducers [10][11][12] (coded F); reaction time: conversion reaction time T 1 (coded G), thickening reaction time T 3 (coded H); reaction temperature: conversion reaction temperature t 1 (coded J), thickening reaction temperature t 3 (coded K), and grinding gap (coded L) during post-treatment [31]. Table 3 also provides the range of values for each factor, where the initial value refers to the values of each factor before optimization, and the maximum and minimum values are the allowable range of values for each factor obtained based on experience.…”
Section: Experimental Designmentioning
confidence: 99%
“…As shown in Table 3, the factors that may affect the tribological properties and service life of lubricating grease during the preparation process of CSCPG are listed, including the proportion of three thickening agents [29]: overbased calcium sulfonate T106A (coded A), polyurea thickening agent (coded C), and composite calcium soap (coded D); base oil 40 • C kinematic viscosity (coded B) [14]; the proportion of the content of the two additives: antioxidant (coded E) [30] and nano-solid friction reducers [10][11][12] (coded F); reaction time: conversion reaction time T 1 (coded G), thickening reaction time T 3 (coded H); reaction temperature: conversion reaction temperature t 1 (coded J), thickening reaction temperature t 3 (coded K), and grinding gap (coded L) during post-treatment [31]. Table 3 also provides the range of values for each factor, where the initial value refers to the values of each factor before optimization, and the maximum and minimum values are the allowable range of values for each factor obtained based on experience.…”
Section: Experimental Designmentioning
confidence: 99%
“…Wu C [29] found that nano-CuO as an additive exhibits better friction reduction performance in polyurea grease than in CSCG. Researchers have also prepared lithium complex-calcium sulfonate greases by mixing lithium composite soap and calcium sulfonate, which have good corrosion resistance for low-carbon steel due to the unique reversed micelles of calcium sulfonate and the sealing function [30].…”
Section: Introductionmentioning
confidence: 99%